1983
DOI: 10.1111/j.1600-0722.1983.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylitol and other carbon sources on the cell wall of Streptococcus mutans

Abstract: – Transferring actively growing bacteria or Streptococcus mutans ATCC 27351 into a xylitol‐containing reaction mixture caused distinct alterations in bacterial ultrastructure without notable effect on the total viability of the strain. Incubations in media containing 50 mg/ml of glucose, fructose, sucrose, lactose, sorbitol or mannitol as the primary carbon source did not affect bacterial ultrastructure. These fermentations were reflected biochemically in the amounts of insoluble glucans, as expected. A negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…The mechanism by which erythritol and xylitol affect total plaque accumulation is not known in detail. For xylitol it is known, however, that a contributing factor may be the reduction in the amount of insoluble, extracellular polysaccharides [Söderling et al, 1987] and lipoteichoic acids [Rølla et al, 1980], and changes in bacterial ultrastructure [Tuompo et al, 1983] observed in plaque or plaque organisms exposed to xylitol. The cultivation tests of this study also suggest that the presence of erythritol in the culture medium exerted relatively strong growth inhibition of mutans streptococci especially after 3-hour cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which erythritol and xylitol affect total plaque accumulation is not known in detail. For xylitol it is known, however, that a contributing factor may be the reduction in the amount of insoluble, extracellular polysaccharides [Söderling et al, 1987] and lipoteichoic acids [Rølla et al, 1980], and changes in bacterial ultrastructure [Tuompo et al, 1983] observed in plaque or plaque organisms exposed to xylitol. The cultivation tests of this study also suggest that the presence of erythritol in the culture medium exerted relatively strong growth inhibition of mutans streptococci especially after 3-hour cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Third, in-vitro studies have shown some strains of oral streptococci take up xylitol and convert it to xylitol-5-phosphate resulting in the development of intra-cellular vacuoles and degraded cell membranes in mutans and sobrinus streptococci, and through this mechanism xylitol is acting in a bacteriostatic way. [55][56][57][58][59] Lastly, some streptococcal strains take up xylitol which participates in what is termed 'the futile metabolic cycle' . [59][60][61][62] In this cycle, xylitol is taken into the cell, phosphorylated to xylitol-5-phosphate, and is then split by sugar-phosphate phosphatases and the resulting xylitol is expelled from the cell.…”
Section: Specific Caries-preventive Actions Of Xylitolmentioning
confidence: 99%
“…[52][53][54] Xylitol can act in a bacteriostatic way: some strains of oral streptococci take up xylitol and convert it to xylitol-5-phosphate, resulting in the formation of intra-cellular vacuoles and degraded cell membranes. [55][56][57][58][59] Xylitol can cause a 'futile metabolic cycle' . Streptococcus strains take up xylitol and phosphorylate it to xylitol -5-phosphate.…”
Section: Non-specificmentioning
confidence: 99%
“…These clinical results have at least partly been attributed to the special inhibitory effect of xylitol on S. mutans. A corner stone of the mechanism seems thus to be a specific relationship between xylitol and S. mutans, as outlined elsewhere [Assev et al, 1983[Assev et al, , 1985Rolla, 1984, 1986a, b;Vadeboncoeur et al, 1983;Tuompo et al, 1983;Assev and Scheie, 1986;Soderling et al, 1987] and which may operate even in the presence of small quantities of sorbitol of Lycasin.…”
mentioning
confidence: 97%